Dermatoglyphic patterns in dementia of the Alzheimer type: a case-control study. Issue 5 (October 1992) - Berr, C; Okra-Podrabinek, N; Feteanu, D; Taurand, S; Hervy, M P; Forette, F; Piette, F; Sebag-Lanoe, R; Alperovitch, A
Abstract : STUDY OBJECTIVE–The aim was to compare digital and palmar dermatoglyphics in subjects with dementia of Alzheimer type and in mentally healthy elderly controls. DESIGN–This design was a case-control study. SETTING–The study was carried out in geriatric units and retirement communities in the Paris area. PARTICIPANTS–Cases were women with clinically diagnosed Alzheimer type dementia according to DSM III-R criteria (n = 82), mainly with late onset of the disease. Controls were women aged 85 years or older without cognitive deterioration (n = 76). MEASUREMENTS AND MAIN RESULTS–Finger and palm prints obtained from both hands by the classical ink method were examined. Fingerprints were classified into four types of figures. On palms, palmar flexion creases, palmar axial triradii, true patterns of the hypothenar area, and main line terminations were described. Examinations were performed by two examiners blind to the subjects's diagnostic category. For the different patterns studied, no major differences between dementia patients and elderly controls were found. Nor was there evidence of high frequencies of features commonly observed in Down's syndrome (trisomy 21), which have previously, though sporadically, been reported. CONCLUSIONS–On one of the largest samples of Alzheimer dementia patients studied, and with evaluation blind to diagnosis, no evidence has been found that particular dermatoglyphic patterns occur like those observed in Down's syndrome, a disease which is related to dementia of the Alzheimer type.